Outcome of Total Hip Replacement with Ceramic on Ceramic Bearings, Case series from Aga Khan University Hospital, Karachi, Pakistan - Khattak, Mujahid Jamil; Ali, Rufina; Hammad Naqi Khan; Ashraf, Umair (Journal of the Pakistan Medical Association, 2021)
Total Hip replacement offers complete resolution of symptoms and restoration of Hip function. The long-term success of hip replacement primarily depends on wear and osteolysis resulting from the bearing surfaces used in hip replacement surgery. Different bearing surfaces have been used in hip replacements with variable success rate. Traditional combinations include, metal on polyethylene, ceramic on Polyethylene and metal on metal articulations. Ceramic on ceramic Bearing couple is a relatively newer combination recommended for younger patients requiring Total hip Arthroplasty. Ceramics have the lowest wear rate and are showing promising long-term results in international literature. We report the use of this bearing surface for the first time in Pakistan. Continuous...